AN ANALYSIS OF ENGLISH PHRASAL VERB USED IN THE LYRICS OF ELVIS PRESLEY’S SONGS - paulus andi perwiratumanggor (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Abstract: The purpose of this research are to find: 1) the types of phrasal verb used in the lyrics of Elvis Presley songs, 2) the characteristics features of phrasal verb used in the lyrics of Elvis Presley songs. This research use descriptive qualitative method. The data were collected by documentation method.In technique of checking trustworthiness of data the researcher used triangulation. The results of this study are 1) the types of phrasal verbs in Elvis Presley’s songs, there are 25 data which has been found by the researcher. The data showed that adverbial phrasal verbs is the most dominant types of phrasal verb in Elvis Presley’s songs, and its about 72%. The lower is prepositional phrasal verbs with the percentages 28, 2) the characteristics feature of phrasal verbs in the lyrics of Elvis Presley’s songs entitled Are you lonesome tonight and Suspicious mind is the combination is not freely formed. Keywords: phrasal verb, lyric, songs, Elvis Presley.